2013
DOI: 10.1103/physrevb.88.035106
|View full text |Cite
|
Sign up to set email alerts
|

Interaction and disorder effects in three-dimensional topological insulator thin films

Abstract: A theory of combined interference and interaction effects on the diffusive transport properties of 3D topological insulator surface states is developed. We focus on a slab geometry (characteristic for most experiments) and show that interactions between the top and bottom surfaces are important at not too high temperatures. We treat the general case of different surfaces (different carrier densities, uncorrelated disorder, arbitrary dielectric environment, etc.). In order to access the lowenergy behavior of th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 125 publications
1
26
0
Order By: Relevance
“…The most striking is the fact that these surface states are described by a Dirac Hamiltonian [1,2], which gives rise to weak antilocalization (WAL) in the presence of scalar disorder [3][4][5]. The WAL correction can be affected by the interaction of the surface states with the residual bulk states [6], the thickness of the film [7], or electron-electron interactions [8,9] changing its sign and turning it into weak localization (WL). At the same time, since 3DTIs have strong spin-orbit coupling, one expects spin-orbit coupled impurities to have a strong effect on transport, different however than in graphene where two valleys are present [10,11].…”
mentioning
confidence: 99%
“…The most striking is the fact that these surface states are described by a Dirac Hamiltonian [1,2], which gives rise to weak antilocalization (WAL) in the presence of scalar disorder [3][4][5]. The WAL correction can be affected by the interaction of the surface states with the residual bulk states [6], the thickness of the film [7], or electron-electron interactions [8,9] changing its sign and turning it into weak localization (WL). At the same time, since 3DTIs have strong spin-orbit coupling, one expects spin-orbit coupled impurities to have a strong effect on transport, different however than in graphene where two valleys are present [10,11].…”
mentioning
confidence: 99%
“…One may notice that there is a weak upturn in all three curves at the lowest temperatures; such an upturn has been reported for TI thin films in the past, [25][26][27] and is discussed to be due to electron interaction effects. 28,29 The R yx (B) curves showed significant and complicated changes when V g is varied. In Fig.…”
mentioning
confidence: 99%
“…We showed that the half-metallic behavior can lead to a pseudospin-valve-like effect in the tunneling current between two TI surfaces, which can be used as a diagnostic for the half-metallic behavior. Our study indicates that weak disorder (which could get induced due to the roughness in surface potentials) can not only affect transport due to scattering of electron due to its coupling with the spin degree of freedom of the disorder potential (which is the one usually considered for study [21]) but also due to its coupling with the frozen pseudospin degree of freedom of the disorder potential. Presence of such disorder may not be seen in the traditional methods used to probe surface states which couple only to the spin texture of the surface states such as the spin polarized ARPES and STM.…”
Section: Resultsmentioning
confidence: 81%